IMPLEMENTASI PROGRAM ENTREPRENEURSHIP DALAM MEWUJUDKAN SEKOLAH MANDIRI FINANSIAL DAN KARIR SISWA SMK DARUL ULUM KEPUHDOKO DI JOMBANG: IMPLEMENTASI PROGRAM ENTREPRENEURSHIP DALAM MEWUJUDKAN SEKOLAH MANDIRI FINANSIAL DAN KARIR SISWA SMK DARUL ULUM KEPUHDOKO DI JOMBANG - Elmuna, Naily; Rachman Hakim, Arie; Ashlihah, Ashlihah (Universitas KH. A. Wahab Hasbullah, 2024)
ABSTRACT Entrepreneurship is the attitude, spirit, and ability to create something new and beneficial for oneself and others. Entrepreneurship programs aim to shape students' character into entrepreneurs with innovative and creative ideas. Vocational High Schools (SMK) support this program to prepare students to become skilled workers in their chosen fields. However, the high number of unemployed SMK graduates is due to the lack of suitable job opportunities. Becoming entrepreneurs can be a solution to reduce unemployment by creating new job opportunities. This research aims to understand the implementation of entrepreneurship programs in improving the financial independence and careers of SMK students at SMK Darul Ulum Kepuhdoko Jombang. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and document studies. The results show that the entrepreneurship program at SMK Darul Ulum Kepuhdoko Jombang is beneficial for students' careers after graduation, covering the fields of Light Vehicle Engineering, Multimedia, and Industrial Chemistry. The implementation of this program enhances the school's finances and equips graduates with entrepreneurial skills, enabling them to create job opportunities. Keywords: Entrepreneurship, Vocational High School